Anoxic storage regenerates reactive Fe(II) in reduced nontronite with short-term oxidation. (15th July 2019) - Liao, Wenjuan; Yuan, Songhu; Liu, Xixiang; Tong, Man
Abstract: Fe(II)-bearing clay minerals represent a large electron source under redox-dynamic systems. Although redox reactions between Fe(II)-bearing clay minerals and oxidants (such as O2 ) have been widely investigated in redox-dynamic systems, one important process that remains unexplored is the response of Fe(II) reactivity in clay minerals to long-term anoxic storage following short-term oxidation. Here we used reduced nontronite NAu-2 as a model Fe-bearing clay mineral, exposed its suspension to air for oxidation in a short time (1, 3 and 5 h), and then stored it under anoxic conditions without any exogenous oxidants for a long time (0–120 h). After different time of anoxic storage, we evaluated the reactivity of Fe(II) by air oxidation, measured the Fe(II) fractions by phosphate extraction and characterized the variation of Fe(II) by X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR) and Mössbauer. We found that anoxic storage increased prominently the rate of Fe(II) oxidation by O2 and the resultant production of hydroxyl radicals, and the increase was more obvious for the NAu-2 with a longer time of anoxic storage. Both phosphate extraction and XPS results revealed that the reactive Fe(II) associated with edge sites was regenerated and the regeneration increased with the increase in anoxic storage time. FTIR and Mössbauer spectra identified the rearrangements of NAu-2 structure during anoxic storage. The mechanism of reactive Fe(II) regeneration by anoxic storage was attributed to the increase in reactive Fe(II) associated with edge sites, which was most likely induced by the electron transfer from Fe(II) at the interior sites to Fe(III) at the edge sites in the octahedral sheets of nontronite. The driving force for electron transfer was presumed to be the redox potential gradient between edge and interior sites because of different Fe(II)/Fe(III) ratios. Our findings improve the understanding of Fe(II)/Fe(III) interconversion as well as the resultant reducing impact on substance transformation induced by Fe(II)-bearing clay minerals under redox-dynamic systems.